Targeting Myeloid-Derived Suppressor Cell, a Promising Strategy to Overcome Resistance to Immune Checkpoint Inhibitors - Hou, Aohan; Hou, Kaiyu; Huang, Qiubo; Lei, Yujie; Chen, Wanling (Frontiers in Immunology, 2020)
Immune checkpoint inhibitors (ICIs) are starting to transform the treatment for patients with advanced cancer. The extensive application of these antibodies for various cancer obtains exciting anti-tumor immune response by activating T cells. Although the encouraging clinical benefit in patients receiving these immunostimulatory agents are observed, numbers of patients still derive limited response or even none for reasons unknown, sometimes at the cost of adverse reactions. Myeloid-derived suppressor cells (MDSCs) is a heterogeneous immature population of myeloid cells partly influencing the efficacy of immunotherapies. These cells not only directly suppress T cell but mediate a potently immunosuppressive network within tumor microenvironment to attenuate the anti-tumor response. The crosstalk between MDSCs and immune cells/non-immune cells generates several positive feedbacks to negatively modulate the tumor microenvironment. As such, the recruitment of immunosuppressive cells, upregulation of immune checkpoints, angiogenesis and hypoxia are induced and contributing to the acquired resistance to ICIs. Targeting MDSCs could be a potential therapy to overcome the limitation. In this review, we focus on the role of MDSCs in resistance to ICIs and summarize the therapeutic strategies targeting them to enhance ICIs efficiency in cancer patients.